KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL PISA KONTEN SPACE AND SHAPE BERDASARKAN TEORI NEWMAN - Pereira, Jerito; Aulingga, Anisa; Ning, Yiting; Vilela, Anastasia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is based on the low level of students completing PISA questions. One of the factors that influence the low number of students in PISA questions is that they are not used to working on problems in real context. The purpose of this study is to describe students' mistakes in solving PISA questions on Space and Shape content based on Newman's Theory, namely: reading errors, misunderstanding, transformation errors, process skill errors and notation errors or writing answers. This study uses descriptive qualitative data collection in the form of images and sentences described. The subjects in this study were eighth grade students of SMP Negeri 9 in Cimahi City. Data collection techniques in this study are by giving a test in the form of PISA questions on Space and Shape content in 2012. Based on the results of the study, showed that students experience errors in process skills caused by the lack of PISA practice exercises which are international assessments, as well as students' weakness in skills mathematics in the form of real contexts.